2015
DOI: 10.18034/abr.v1i2.321
|View full text |Cite
|
Sign up to set email alerts
|

Career Preference of Business Graduate in Bangladesh: A Case Study of Some Selected Private Universities

Abstract: This paper attempts to investigate the career preference of business graduates of private universities in Bangladesh. A total number of 256 final year business students, irrespective of gender in 15 private universities located in Dhaka city have been interviewed. Majority of the respondents' preferred field for future career development are banks and multinational companies. More than average of the total respondents plans to seek employment in their chosen field specially after obtaining the bachelor's degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…Students who are studying at private schools in Kazakhstan can be related to the higher economic status of families, because in Kazakhstan tuition payment for private schools can vary from USD 250 to 1000 per month while the living wage in Kazakhstan is USD 78.72 per month [72]. Students who are studying in private schools prefer a future career: business, entrepreneurship, law, finance, etc., rather than STEM [73][74][75]. This finding was also confirmed in some other papers [68,69], they found that economically disadvantaged students tended to have more trust in STEM majors, more than their high-income counterparts.…”
Section: Schools Type and Location And Stem Career Interestsupporting
confidence: 81%
“…Students who are studying at private schools in Kazakhstan can be related to the higher economic status of families, because in Kazakhstan tuition payment for private schools can vary from USD 250 to 1000 per month while the living wage in Kazakhstan is USD 78.72 per month [72]. Students who are studying in private schools prefer a future career: business, entrepreneurship, law, finance, etc., rather than STEM [73][74][75]. This finding was also confirmed in some other papers [68,69], they found that economically disadvantaged students tended to have more trust in STEM majors, more than their high-income counterparts.…”
Section: Schools Type and Location And Stem Career Interestsupporting
confidence: 81%
“…Additional tests are also performed to determine whether there is any significant difference in intrinsic motivation, extrinsic motivation, subjective norms and self-efficacy between the two types of institutions. The results in Table 05 shows that there is no significant difference in the students' intention to become professional accountants between the private and public university students (p>0.05), and it is contradicted from Hossain and Siddique (2012). Therefore, H2 is rejected.…”
Section: Test Of Significant Differencementioning
confidence: 95%
“…This study emphasized the importance of understanding job preferences and the factors influencing career choice, and could be useful in ensuring a future balance between professional domains and meeting society's evolving expectations. Another study was conducted by Hossain and Siddique (2012) to investigate the career preference of business graduates of private universities in Bangladesh. A total number of 256 final year business students, irrespective of gender in 15 private universities located in Dhaka city have been interviewed.…”
Section: Review Of Literaturementioning
confidence: 99%